A Descriptive Study of a Turkish Pneumoconiosis Case-Series - Sarı, Gülden; Şimşek, Cebrail (La Medicina del Lavoro, 2023)
Background: The study aimed to examine the conditions and factors affecting pneumoconiosis cases to determine the dimensions of the pneumoconiosis problem. Methods: This retrospective study was conducted in a tertiary research hospital between January 1, 2014, and December 31, 2021. Five hundred ninety-seven patients with pneumo- coniosis were included in the study. Results: Large opacities were detected in 157 cases. When we compared cases with and without Pulmonary Massive Fibrosis (PMF), age and concomitant pulmonary disease were higher in PMF cases, which also showed lower FEV1, FVC, and FEV1/FVC. PMF was more frequent in subjects with long dust exposure duration (more than 20 years) and concomitant pulmonary diseases, particularly tuberculosis. Three occupations, sandblasters, dental technicians, and ceramic workers, showed the earliest onset of pneumoconiosis. Conclusions: The study presents pneumoconiosis data in a mixed and large population and contributes to the imple- mentation of evidence-based policies and interventions for countries like Turkey striving to cope with the problem of pneumoconiosis.